A Generalized Observer for Estimating Fast-Varying Disturbances - Ton Duc Do; Hoach The Nguyen (My University, 2018)
The paper introduces a Generalized Disturbance Observer (GDO) capable of estimating a broad class of disturbances, including fast-varying types. Unlike conventional disturbance observers or FVDOs, the proposed GDO does not rely on conservative assumptions like zero time-derivatives. The authors provide systematic rules for gain tuning and design of observer weighting matrices. Validated in linear and nonlinear system simulations and experimentally applied to wind energy systems with LQR control, the GDO shows bounded stability and superior performance relative to traditional approaches
Keywords: generalized disturbance observer; fast-varying disturbances; estimation error; wind energy conversion systems; control theory; MATLAB simulations